(Re-)Construction of Identity and Belonging after Forced Migration: A Sociology of Knowledge Approach. (29th April 2022) - Mijić, Ana
Abstract: This study uses a sociology of knowledge perspective to analyse how former Bosnian refugees in Austria have integrated the experiences of ethnicized war and forced migration into their lives over the past three decades. The objective hermeneutical analysis of narrative interviews with Bosnian-Austrians reveals significant differences between former child refugees and those who experienced war and migration as adolescents. From a sociology of knowledge perspective, these differences can be attributed to varying 'stratifications of experience': The central crisis in the adolescents' lives was triggered by experiencing the destruction of their Yugoslavian life-world, which significantly eroded their trust in their social reality's stability and in their belonging. The former child refugees, however, particularly struggle with their double marginalization. While the former typically manage this crisis through an exaggerated adherence to the ideal of personal performance, the latter draw on collective imaginations of ethnic/national affiliation and try to comply with them.